2017
DOI: 10.3389/fpls.2017.00971
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Genes Associated with the Artemisinin Biosynthesis by Jasmonic Acid Treatment under the Light in Artemisia annua

Abstract: Artemisinin is a sesquiterpene lactone endoperoxide extracted from a traditional Chinese medicinal plant Artemisia annua. Artemisinin-based combination therapies (ACTs) are recommended as the best treatment of malaria by the World Health Organization (WHO). Both the phytohormone jasmonic acid (JA) and light promote artemisinin biosynthesis in A. annua. Interestingly, we found that the increase of artemisinin biosynthesis by JA was dependent on light. However, the relationship between the two signal pathways me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 57 publications
(85 reference statements)
2
45
0
Order By: Relevance
“…Gibberellins are important diterpenoid acid plant hormones that play roles in promoting the biosynthesis of artemisinin [29,49]. In addition, to phytohormones, it has also been found that light has an in uence on the accumulation of artemisinin [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibberellins are important diterpenoid acid plant hormones that play roles in promoting the biosynthesis of artemisinin [29,49]. In addition, to phytohormones, it has also been found that light has an in uence on the accumulation of artemisinin [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the activities of different hormones can be in uenced to varying degrees by light, and thus light and hormones may jointly regulate various processes in plants [21,[26][27][28]. For example, Hao et al [29] demonstrated the co-regulation of artemisinin biosynthetic pathway genes under light and jasmonic acid treatment, with the accumulation of artemisinin in response to jasmonic acid treatment being dependent on light, and identi ed eight transcription factors (TFs) as candidate genes regulating the cross-talk light and jasmonic acid signals in artemisinin biosynthesis. Along similar lines, we wished to determine whether ultraviolet B irradiation and phytohormone gibberellins could coordinately regulate the accumulation of artemisinin in A. annua.…”
mentioning
confidence: 99%
“…cDNA was synthesized from 1.0 µg of total RNA using PrimeScript TM RT Master Mix (Takara, Shiga, Japan). The transcript levels of AabHLH1 and artemisinin biosynthetic genes ( AaADS , AaCYP71AV1 , AaDBR2 , and AaALDH1 ) were analyzed by qRT‐PCR as described previously . SYBR Green qPCR Master Mix (Tiangen, Beijing, China) and a Roche Light Cycler 96 Real‐Time PCR System (Roche, Basel, Switzerland) were used for qRT‐PCR according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Three technical replicates were analyzed. Relative gene expression levels were determined by the 2 −ΔΔCt method and the A. annua Actin gene was used as an internal control . All primer sequences used are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation